Gait maturation in children with cerebral palsy: A pilot study - J.S. Marques; P. Roquetti Fernandes; J. Fernandes Filho; F. B. Policarpo (Desafio Singular, 2011)
This study aimed at observing children with cerebral palsy's (CP) gait maturation and to correlate gait maturation's motor skill parameters. Podogram and video shooting of eight children's gait were used. Children up to seven years of age participated in the study. Cluster analysis was applied, dividing the sample into two groups, using the relation between pelvis' width and the spreading of the ankles (REL) as parameters. Data were analyzed using t-test, analysis of Deltas, and Pearson's correlation. Deviance from normality for all the parameters was demonstrated with greater failure in speed and cadence and a significant correlation among these parameters, and yet between them and the REL parameter. Although children with CP had acquired gait, they still do it immaturely.